2022
DOI: 10.3390/ijerph19063718
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Industrial Structure Upgrading on Green Total Factor Productivity in the Yangtze River Economic Belt

Abstract: The Yangtze River economic belt is an inland river economic belt with international influence composed of 11 provinces and municipalities in the Yangtze River Basin. This paper uses the super-efficiency model to calculate the green total factor productivity of 11 provinces and municipalities in the Yangtze River economic belt (YREB). Then we establish a model to study the impact of industrial structure upgrading, industrial structure rationalization, and environmental regulation on green total factor productiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…In addition, some scholars have also proved with the strong Porter hypothesis that stricter environmental policies improve growth and the environment and induce profitable innovation [5]. Moreover, some studies used Chinese panel data to conduct empirical tests and found that higher environmental regulation intensity could promote technological progress and green total factor productivity, which supports the Porter hypothesis [6][7][8][9].…”
Section: Introductionmentioning
confidence: 85%
“…In addition, some scholars have also proved with the strong Porter hypothesis that stricter environmental policies improve growth and the environment and induce profitable innovation [5]. Moreover, some studies used Chinese panel data to conduct empirical tests and found that higher environmental regulation intensity could promote technological progress and green total factor productivity, which supports the Porter hypothesis [6][7][8][9].…”
Section: Introductionmentioning
confidence: 85%
“…The entropy weight TOPSIS method is a combination of the entropy weight and TOPSIS. The entropy weight was used to assign the weights of evaluation indicators, which was based on the degree of variability of the evaluation indicators, thus avoiding the influence of bias caused by human factors [ 5 ]. The order preference by similarity to ideal solution (TOPSIS) method, also known as the distance method of superiority and inferiority solution, is a multi-attribute decision-making method.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, how to decouple regional economic development from environmental pollution and promote the synergistic development of the economy, society, and eco-environment are still important issues [ 4 ]. As an important strategic region in China [ 5 , 6 ], the Yangtze River Economic Belt has become one of the leading demonstration areas for the green transformation of China’s economic development due to its resource endowment and high industrial agglomeration. In the context of China’s comprehensive promotion of green development, taking the Yangtze River Economic Belt as the research area to explore the temporal and spatial evolution characteristics and influencing factors of its green development performance is of great practical significance for China to further promote green development.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the “structural dividend” released by industrial-structure upgrading can promote the emergence of clean industries and provide effective support to improve GTFP. Wang et al (2018), Zhu et al (2019), and Sun et al (2022) have further maintained that industrial-structure upgrading can significantly improve urban GTFP in the context of environmental regulation, energy control, and low-carbon city construction [ 48 , 49 , 50 ]. Accordingly, we propose the following research hypothesis:…”
Section: Theoretical Analysis and Research Hypothesesmentioning
confidence: 99%
“…According to the above analysis, it is clear that both specialized and diversified agglomeration of productive services can directly promote GTFP through agglomeration externalities. Meanwhile, some theoretical and empirical studies have shown that industrial-structure upgrading is an important inducement to promote regional GTFP [ 46 , 48 , 50 ]. Considering the influence of economic-development level and industrial type, specialized agglomeration can improve GTFP through industrial-structure upgrading, while this transmission path has not been confirmed in diversified agglomeration.…”
Section: Theoretical Analysis and Research Hypothesesmentioning
confidence: 99%